Organic silicon composition, preparation method and thermal interface material
By using the polysiloxane matrix and tackifier in the silicone composition, combined with the thermally conductive inorganic filler and catalyst, the contradiction between thermal interface material in thermal conductivity and adhesion is solved, and an efficient heat conduction effect is achieved.
Patent Information
- Application Number
- CN202411675253.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult for existing thermal interface materials to achieve high bonding energy and high thermal conductivity at the same time, resulting in low thermal conductivity at the interface.
Using an organic silicon composition, the composition comprising a polysiloxane matrix, a thermally conductive inorganic filler, a catalyst and a tackifier, by adjusting the vinyl and hydrogen silicon content in the polysiloxane matrix, and adding a tackifier to form a thermal interface material with high thermal conductivity and high adhesion.
It achieves high thermal conductivity and high adhesion of thermal interface materials, improves the heat conduction efficiency at the interface, and is suitable for electronic packaging, solar thermal phase change, batteries and medicine fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermal interface materials, and in particular to an organic silicon composition and a preparation method thereof, and a thermal interface material. Background Art
[0002] Currently, in applications in many fields such as electronic packaging, solar thermal phase change, batteries and medicine, the adhesion between interfaces plays a vital role in the heat conduction between interfaces. Compared with other adhesive materials, thermal interface materials are favored due to their ability to provide good contact between surfaces and dissipate energy under stress. Nevertheless, the low thermal conduction efficiency at the interface has always been a problem that plagues electronic devices. Since organic / inorganic interfaces usually have poor thermal conductivity and the size of nanodevices is getting smaller and smaller, the interface is likely to become a bottleneck for heat transfer.
[0003] Thermal interface materials generally include a resin matrix and thermally conductive inorganic fillers. The addition of thermally conductive inorganic fillers can improve the thermal conductivity of the interface material, but as the amount of thermally conductive inorganic fillers increases, its adhesion will become longer. How to balance the contradiction between the high adhesion and high thermal conductivity of thermal interface materials is an issue that urgently needs to be solved in current research. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a silicone composition and a preparation method thereof, and a thermal interface material, aiming to solve the problem that existing thermal interface materials cannot achieve high bonding energy and high thermal conductivity.
[0005] The first aspect of the embodiment of the present application provides an organosilicon composition, comprising: a polysiloxane matrix, a thermally conductive inorganic filler, a catalyst and a tackifier;
[0006] The polysiloxane matrix includes a bisvinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl groups in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol;
[0007] The mass percentage of the thermally conductive inorganic filler to the polysiloxane matrix is 70% to 110%;
[0008] The ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the adhesion promoter is 0.1% to 1%;
[0009] The tackifier includes a hydrogenated silicone resin grafted acrylate tackifier; the content of the vinyl group in the tackifier in the composition is Z mol;
[0010] Among them, X:Y is 1:(1.5 to 6), and Z:(YX) is (0.01 to 0.6):1.
[0011] In some embodiments of the present application, the tackifier includes a tackifier having a structure as shown in Formula 1 below:
[0012]
[0013] Among them, 0 <b≤10,0<c≤10。
[0014] In some embodiments of the present application, the Z: (YX) is (0.25 to 0.4); and / or
[0015] The X:Y is 1:(2.5 to 3.5); and / or
[0016] The concentration of vinyl groups in the bis-vinyl-terminated polydimethylsiloxane is 0.1wt%-10wt%; and / or
[0017] The concentration of hydrogen atoms bonded to silicon atoms in the terminal hydrogen-containing polydimethylsiloxane is 0.01 wt % to 2 wt %.
[0018] In some embodiments of the present application, the thermally conductive inorganic filler accounts for 85% to 95% by mass of the polysiloxane matrix; and / or
[0019] The thermally conductive inorganic filler is selected from at least one of aluminum powder, aluminum oxide, aluminum nitride powder, boron nitride powder, silicon dioxide powder, zinc oxide, aluminum hydroxide, and magnesium hydroxide; and / or
[0020] The particle size of the thermally conductive inorganic filler is 0.1 μm to 100 μm.
[0021] In some embodiments of the present application, the ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the adhesion promoter is 0.2% to 0.5%; and / or
[0022] The catalyst includes a platinum catalyst.
[0023] A second aspect of the present application provides a method for preparing an organosilicon composition, the preparation method comprising the following steps:
[0024] Mixing a thermally conductive inorganic filler with a polysiloxane matrix to obtain a first mixture;
[0025] adding a tackifier and a catalyst to the first mixture to obtain the organosilicon composition;
[0026] The polysiloxane matrix comprises a bisvinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl groups in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol; the tackifier comprises a hydrogen-containing silicone resin grafted acrylate tackifier; the content of vinyl groups in the tackifier in the composition is Z mol;
[0027] Among them, X:Y is 1:(1.5 to 6), and Z:(YX) is (0.01 to 0.6):1.
[0028] In some embodiments of the present application, the preparation method includes:
[0029] The inorganic filler and the polysiloxane matrix are mixed by first stirring to obtain a first mixture, wherein the rotation speed of the first stirring is 700 r / min to 900 r / min, and the stirring time of the first stirring is 0.5 min to 10 min; and / or
[0030] The tackifier and the catalyst are added to the first mixture, and the organic silicon composition is obtained by second stirring and third stirring; the second stirring speed is 700 r / min to 900 r / min, and the stirring time of the second stirring is 0.5 min to 10 min; the third stirring speed is 950 r / min to 1100 r / min, and the stirring time of the second stirring is 0.2 min to 1 min; and / or
[0031] The structure of the tackifier is shown in Formula 1 below:
[0032]
[0033] Among them, 0 <b≤10,0<c≤10。
[0034] A third aspect of the present application provides a thermal interface material, which is formed by curing the composition or the composition obtained by the preparation method.
[0035] In some embodiments of the present application, the composition is cured to form the thermal interface material after reacting at a temperature of 80° C. to 200° C. for 1 hour to 24 hours; and / or
[0036] The curing process of the composition includes a first curing stage and a second curing stage; the curing temperature of the first curing stage is 80°C to 90°C, and the reaction time of the first curing stage is 1h to 4h; the curing temperature of the second curing stage is 140°C to 160°C, and the reaction time of the second curing stage is 0.5h to 2h.
[0037] In some embodiments of the present application, the thermal conductivity of the thermal interface material is 9W m -1 K -1 Up to 14W m -1 K -1 ; and / or
[0038] The bonding work of the thermal interface material is 650 J m -2 Up to 2300 J m -2 .
[0039] Beneficial effects of this application:
[0040] The organic silicon composition in the present application includes a divinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl in the polysiloxane matrix is Xmol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Ymol, and X:Y is controlled to be 1:(1.5 to 6), so that the composition can have a high content of thermally conductive inorganic filler, and the thermal interface material obtained after curing has high adhesion. At the same time, a hydrogen-containing silicone resin grafted acrylate tackifier is also added to the organic silicon composition of the present application. The acrylate side chains in the tackifier can easily diffuse to the surface of the thermal interface material, thereby facilitating the increase of the adhesion of the thermal interface material; at the same time, the specific content of vinyl in the tackifier can participate in the formation of a cross-linked network together with the hydrogen atoms and vinyl in the polysiloxane matrix bonded to silicon atoms, and the main chain of the tackifier interacts with the main chain of the polysiloxane matrix, which is conducive to further increasing the adhesion and thermal conductivity of the thermal interface material obtained after curing. DETAILED DESCRIPTION
[0041] The technical solutions of the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0043] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0044] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0045] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0046] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0047] Currently, in applications in many fields such as electronic packaging, solar thermal phase change, batteries and medicine, the adhesion between interfaces plays a vital role in the heat conduction between interfaces. Compared with other adhesive materials, thermal interface materials are favored due to their ability to provide good contact between surfaces and dissipate energy under stress. Nevertheless, the low thermal conduction efficiency at the interface has always been a problem that plagues electronic devices. Since the organic / inorganic interface usually has poor thermal conductivity and the size of nanodevices is getting smaller and smaller, the interface is likely to become a bottleneck for heat transfer.
[0048] Thermal interface materials generally include a resin matrix and thermally conductive inorganic fillers. Increasing the proportion of thermally conductive inorganic fillers in thermal interface materials can improve the thermal conductivity of the interface material, but as the amount of thermally conductive inorganic fillers increases, its adhesion becomes longer, that is, increasing the thermal conductivity of the interface material will lead to a decrease in its adhesion. How to balance the contradiction between the bonding energy and thermal conductivity of the thermal interface material so that it has high bonding energy and high thermal conductivity is an urgent problem to be solved in current research.
[0049] In view of this, the embodiments of the present application provide a silicone composition, a preparation method, and a thermal interface material. The thermal interface material obtained after curing the silicone composition provided in the embodiments of the present application has high bonding energy and high thermal conductivity. The silicone composition, preparation method, and thermal interface material in the present application are described below in combination with specific embodiments and experimental test results.
[0050] The embodiments of the present application provide an organosilicon composition, which has high adhesion and high thermal conductivity after being cured, and can be used in multiple fields such as electronic packaging, solar thermal phase change, batteries and medicine.
[0051] Specifically, the silicone composition in the embodiment of the present application includes: a polysiloxane matrix, a thermally conductive inorganic filler, a catalyst, and a tackifier. The polysiloxane matrix includes a bis-vinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl in the polysiloxane matrix is Xmol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Ymol; the mass percentage of the thermally conductive inorganic filler to the polysiloxane matrix is 70% to 110%; the ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the tackifier is 0.1% to 1%; the tackifier includes a hydrogen-containing silicone resin grafted acrylate tackifier; the content of vinyl from the tackifier in the composition is Zmol; wherein X:Y is 1:(1.5 to 6), and Z:(YX) is (0.01 to 0.6):1.
[0052] Exemplarily, X:Y is 1:1.5, 1:2.0, 1:2.5, 1:3.0, 1:3.5, 1:4.0, 1:4.5, 1:5.0, 1:5.5, 1:6.0 and values between any two of the above values. Further, X:Y is 1:(2.5 to 3.5).
[0053] Exemplarily, Z:(YX) is 0.01:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1 and values between any two of the above values. Further, Z:(YX) is (0.25 to 0.55):1.
[0054] Exemplarily, the mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix is 70%, 75%, 80%, 85%, 90%, 95%, 100%, 105%, 110% and values between any two of the above values. Taking the mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix as 70% as an example, assuming that the mass of the polysiloxane matrix is 100 parts, the number of parts of the thermally conductive inorganic filler is 70 parts.
[0055] Exemplarily, the ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the tackifier is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% and values between any two of the above values. Further, the ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the tackifier is 0.2% to 0.5%. Taking the ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the tackifier as 0.1% as an example, assuming that the sum of the mass of the polysiloxane matrix and the tackifier is 100 parts, the number of parts of the catalyst is 0.1 parts.
[0056] The silicone composition in the embodiment of the present application includes a divinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl groups in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol, and X:Y is controlled to be 1:(1.5 to 6), so that the composition can have a high content of thermally conductive inorganic filler, and the thermal interface material obtained after curing has high adhesion.
[0057] At the same time, a hydrogenated silicone resin grafted acrylate tackifier is also added to the silicone composition of the present application. The acrylate side chains in the tackifier can easily diffuse to the surface of the thermal interface material, thereby helping to increase the adhesion performance of the thermal interface material; at the same time, the specific content of vinyl in the tackifier can participate in the formation of a cross-linked network together with the hydrogen atoms and vinyls bonded to the silicon atoms in the polysiloxane matrix, and the main chain of the tackifier and the main chain of the polysiloxane matrix interact with each other, which is beneficial to further increase the adhesion and thermal conductivity of the thermal interface material obtained after curing.
[0058] It is understandable that, since the polysiloxane matrix includes bisvinyl-terminated polydimethylsiloxane, and the bisvinyl-terminated polydimethylsiloxane has a vinyl functional group, the content of vinyl in the polysiloxane matrix can be adjusted by changing the content of bisvinyl-terminated polydimethylsiloxane in the polysiloxane matrix. Exemplarily, the concentration of vinyl in the bisvinyl-terminated polydimethylsiloxane is 0.1wt%-10wt%. Specifically, the concentration of vinyl in the bisvinyl-terminated polydimethylsiloxane is 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% and the value between the above two numerical values, which is not limited here. It should be noted that the bisvinyl-terminated polydimethylsiloxane in the present application can be the existing bisvinyl-terminated polydimethylsiloxane on the market, and the bisvinyl-terminated polydimethylsiloxane in the present application can also be obtained according to the existing preparation process, which is not limited here.
[0059] Similarly, since the polysiloxane matrix includes end-side hydrogenated polydimethylsiloxane, and the end-side hydrogenated polydimethylsiloxane has a silicon-hydrogen functional group located at the end (i.e., a hydrogen atom bonded to a silicon atom), the content of the silicon-hydrogen functional group located at the end in the polysiloxane matrix can be adjusted by changing the content of the end-side hydrogenated polydimethylsiloxane in the polysiloxane matrix. Exemplarily, the concentration of the hydrogen atoms bonded to the silicon atom in the end-side hydrogenated polydimethylsiloxane is 0.01wt%-2wt%. Specifically, the concentration of the hydrogen atoms bonded to the silicon atom in the end-side hydrogenated polydimethylsiloxane is 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt% and values between the above two values, which are not limited here. It should be noted that the terminal side hydrogen-containing polydimethylsiloxane in the present application can be any terminal side hydrogen-containing polydimethylsiloxane currently available on the market, and is not limited here.
[0060] In some embodiments of the present application, the mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix is 85% to 95%. Exemplarily, the mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix is 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% and values between any two of the above values.
[0061] In some embodiments of the present application, the thermally conductive inorganic filler is selected from at least one of aluminum powder, aluminum oxide, aluminum nitride powder, boron nitride powder, silicon dioxide powder, zinc oxide, aluminum hydroxide, and magnesium hydroxide.
[0062] In some embodiments of the present application, the particle size of the thermally conductive inorganic filler is 0.1 μm to 100 μm. Exemplarily, the particle size of the thermally conductive inorganic filler is 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, and values between any two of the above values.
[0063] In some embodiments of the present application, the catalyst is a platinum catalyst. Of course, in other embodiments of the present application, the catalyst may also be a catalyst other than a platinum catalyst, which is not limited here.
[0064] In some embodiments of the present application, the tackifier includes a tackifier having a structure as shown in Formula 1 below:
[0065]
[0066] Among them, 0 <b≤10,0<c≤10。
[0067] The present application also provides a method for preparing an organosilicon composition, characterized in that the preparation method comprises the following steps:
[0068] Step 1: Mixing a thermally conductive inorganic filler with a polysiloxane matrix to obtain a first mixture, wherein the polysiloxane matrix includes a bisvinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol; and X:Y is 1:(1.5 to 6).
[0069] Specifically, the inorganic filler and the polysiloxane matrix are mixed by first stirring to obtain a first mixture, the rotation speed of the first stirring is 700 r / min to 900 r / min, and the stirring time of the first stirring is 0.5 min to 10 min.
[0070] Step 2: Add a tackifier and a catalyst to the first mixture to obtain the silicone composition: wherein the tackifier includes a hydrogenated silicone resin grafted acrylate tackifier; the content of vinyl groups in the composition from the tackifier is Z mol, and satisfies Z:(YX) is (0.01 to 0.6):1.
[0071] Specifically, the tackifier and the catalyst are added to the first mixture to obtain the silicone composition through second stirring and third stirring; the rotation speed of the second stirring is 700 r / min to 900 r / min, and the stirring time of the second stirring is 0.5 min to 10 min; the rotation speed of the third stirring is 950 r / min to 1100 r / min, and the stirring time of the second stirring is 0.2 min to 1 min.
[0072] It should be noted that the thermally conductive inorganic filler, the polysiloxane matrix, the tackifier and the catalyst have been introduced in detail above and will not be described in detail here.
[0073] The embodiment of the present application also provides a thermal interface material, which is formed by curing the composition or the composition obtained by the preparation method. Exemplarily, the composition is cured at a temperature of 80°C to 200°C for 1h to 24h to form the thermal interface material. For another example, the curing process of the composition includes a first curing stage and a second curing stage; the curing temperature of the first curing stage is 80°C to 90°C, and the reaction time of the first curing stage is 1h to 4h; the curing temperature of the second curing stage is 140°C to 160°C, and the reaction time of the second curing stage is 0.5h to 2h.
[0074] Example 1
[0075] (1) Preparation of Thickener 1
[0076] In a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a constant speed stirrer and a thermometer, 30 g of TPGDA (tripropylene glycol diacrylate), 0.10 g of MEHQ inhibitor, 30 g of isopropanol and 0.3 g of chloroplatinic acid were added. The mixture was stirred at a high temperature of 50 ° C and a speed of 250 r / min for 45 minutes. Subsequently, 66 g of HMQ silicone resin was mixed with 20 g of isopropanol and added dropwise to the four-necked flask for 60 minutes. After the addition was completed, the reaction temperature continued to rise for a period of time. The reaction mixture was then cooled to 25 ° C, and 20 g of activated carbon was added and stirred for 5 hours. Finally, a transparent acrylate functionalized MQ silicone resin (No. tackifier 1) was obtained by filtration and vacuum distillation.
[0077] (2) Preparation of thermal interface materials
[0078] First, a preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed uniformly to obtain a polysiloxane matrix, wherein the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, and the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared tackifier (i.e., tackifier 1) and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added tackifier is Zmol, Z:(YX) is 0.1, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the tackifier and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0079] Example 2
[0080] (2) Preparation of thermal interface materials
[0081] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.2, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0082] The difference from Example 1 is that Z:(YX) is 0.2.
[0083] Example 3
[0084] (2) Preparation of thermal interface materials
[0085] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0086] The difference between this embodiment and Example 1 is that Z:(YX) is 0.3.
[0087] Example 4
[0088] (2) Preparation of thermal interface materials
[0089] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.4, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0090] The difference from Example 1 is that Z:(YX) is 0.4.
[0091] Example 5
[0092] (2) Preparation of thermal interface materials
[0093] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.5, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0094] The difference between this embodiment and Example 1 is that Z:(YX) is 0.5.
[0095] Example 6
[0096] (2) Preparation of thermal interface materials
[0097] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.5, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0098] The difference from Example 1 is that Z:(YX) is 0.6.
[0099] Example 7
[0100] (1) Preparation of Thickener 2
[0101] In a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a constant speed stirrer and a thermometer, 10.16 g of methyl methacrylate, 30 g of isopropanol and 0.3 g of chloroplatinic acid were added. The mixture was stirred at a high temperature of 50°C and a speed of 250 r / min for 45 minutes. Subsequently, 66 g of HMQ silicone resin was mixed with 20 g of isopropanol and added dropwise to the four-necked flask for 60 minutes. After the addition was completed, the reaction temperature continued to rise for a period of time. The reaction mixture was then cooled to 25°C, and an appropriate amount of activated carbon was added and stirred for 5 hours. Finally, a transparent methacrylate functionalized MQ silicone resin (No. tackifier 2) was obtained by filtration and vacuum distillation.
[0102] (2) Preparation of thermal interface materials
[0103] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0104] The difference between the embodiment 1 and the embodiment 3 is that the thickener 2 is used to replace the thickener 1 in the embodiment 3.
[0105] Example 8
[0106] (1) Preparation of Thickener 3
[0107] In a four-necked flask equipped with a reflux condenser, a constant pressure dropping funnel, a constant speed stirrer and a thermometer, 48.45 g of epoxy acrylate, 0.10 g of MEHQ inhibitor, 30 g of isopropanol and 0.3 g of chloroplatinic acid were added. The mixture was stirred at a high temperature of 50 ° C and a speed of 250 r / min for 45 minutes. Subsequently, 66 g of HMQ silicone resin was mixed with 20 g of isopropanol and added dropwise to the four-necked flask for 60 minutes. After the addition was completed, the reaction temperature continued to rise for a period of time. The reaction mixture was then cooled to 25 ° C, and 20 g of activated carbon was added and stirred for 5 hours. Finally, a transparent epoxy acrylate functionalized MQ silicone resin (No. tackifier 3) was obtained by filtration and vacuum distillation.
[0108] (2) Preparation of thermal interface materials
[0109] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0110] The difference between the embodiment 1 and the embodiment 3 is that the thickener 1 in the embodiment 3 is replaced by the thickener 3.
[0111] Example 9
[0112] (2) Preparation of thermal interface materials
[0113] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:2. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0114] The difference between this embodiment and embodiment 3 is that X:Y is 1:2.
[0115] Example 10
[0116] (2) Preparation of thermal interface materials
[0117] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:4. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0118] The difference between this embodiment and embodiment 3 is that X:Y is 1:4.
[0119] Embodiment 11
[0120] (2) Preparation of thermal interface materials
[0121] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:5.5. Subsequently, a spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of the spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and the catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z:(YX) is 0.3, and the amount of the catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then stir for 20s at a speed of 1000r / min. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0122] The difference between this embodiment and embodiment 3 is that X:Y is 1:5.5.
[0123] Example 12
[0124] (2) Preparation of thermal interface materials
[0125] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, boron nitride powder is added to the polysiloxane matrix, the mass fraction of boron nitride in the polysiloxane matrix is 70%, and it is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z: (YX) is 0.3, and the amount of catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then transfer to stirring at a speed of 1000r / min for 20s. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0126] The difference between the embodiment 1 and the embodiment 1 is that the thermally conductive inorganic filler is boron nitride, and the mass fraction of boron nitride in the polysiloxane matrix is 70%.
[0127] Embodiment 13
[0128] (2) Preparation of thermal interface materials
[0129] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, magnesium hydroxide is added to the polysiloxane matrix, the mass fraction of magnesium hydroxide in the polysiloxane matrix is 110%, and it is stirred for 60s at a speed of 800r / min. Finally, the prepared thickener and catalyst chloroplatinic acid are added to the mixture, wherein the C=C double bond content in the added thickener is Zmol, Z: (YX) is 0.3, and the amount of catalyst chloroplatinic acid added is 0.3% of the total mass of the thickener and the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then transfer to stirring at a speed of 1000r / min for 20s. Finally, the mixture was cured at a low temperature of 80°C for 2 hours to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1 hour to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0130] The difference between the embodiment 1 and the embodiment 1 is that the thermally conductive inorganic filler is magnesium hydroxide, and the mass fraction of magnesium hydroxide in the polysiloxane matrix is 110%.
[0131] Comparative Example 1
[0132] (2) Preparation of thermal interface materials
[0133] First, the preset content of double-terminal vinyl siloxane and side hydrogen siloxane is mixed evenly to obtain a polysiloxane matrix, in which the content of vinyl in the polysiloxane matrix is Xmol, the content of hydrogen atoms bonded to silicon atoms is Ymol, and X:Y is 1:3. Subsequently, spherical aluminum filler is added to the polysiloxane matrix, the mass fraction of spherical aluminum filler in the polysiloxane matrix is 90%, and the mixture is stirred at a speed of 800r / min for 60s. Finally, the catalyst chloroplatinic acid is added to the mixture, and the amount of catalyst chloroplatinic acid added is 0.3% of the total mass of the polysiloxane matrix. Stir for 60s at a speed of 800r / min, and then transfer to 1000r / min and stir for 20s. Finally, the mixture is at a low temperature of 80°C for 2h to allow the polymer matrix to slowly and evenly cure, and then transferred to 150°C for curing for 1h to obtain a thermal interface material with high adhesion and high thermal conductivity.
[0134] The difference between this embodiment and Example 1 is that no viscosity enhancer is added.
[0135] Experimental testing
[0136] (1) Thermal conductivity test:
[0137] The standard test method for determining vertical thermal conductivity by steady-state method. The test instrument is LW-9389TIM resistance and conductivity meter. The specific steps are as follows: place three thermal interface materials of different thicknesses between the instrument bars, establish a stable heat flow through the components, and measure the thermal resistance R Total The relationship between the thickness BLT and the thermal conductivity κ of the thermal interface material is obtained by linear fitting. TIM And the contact thermal resistance R Contact :
[0138] R Total =R Contact +BLT / κTIM
[0139] (2) Adhesion test:
[0140] The bonding properties of the samples were measured by Shimadzu universal testing machine (SUNS UTM4000). The lap shear bonding test was performed on an Al surface with an overlapping surface area of 12 mm × 12 mm. Specifically, the pre-cured sample was directly applied to the Al surface; then, another piece of Al was placed on top, kept together for 1 minute, and hot pressed at 150°C for 4 hours.
[0141] The thermal conductivity and bonding work of the thermal interface material of the experimental example were tested according to the above method, and the test results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] From the test results of Examples 1 to 13 and Comparative Example 1 in Table 1, it can be seen that adding a certain amount of hydrogenated silicone resin grafted acrylate tackifier to the silicone composition can improve the thermal conductivity and bonding work of the thermal interface material formed after the composition is cured.
[0146] From the test results of Example 1, Example 7 and Example 8, it can be seen that the tackifier is tripropylene glycol diacrylate functionalized MQ silicone resin (ie, tackifier 1), which is beneficial to further improve the thermal conductivity and bonding work of the thermal interface material formed after the composition is cured.
[0147] From the test results of Examples 1 to 6, it can be seen that when the amount of tackifier added satisfies X:Y of about 1:3 and Z:(YX) of (0.25 to 0.45):1, especially when Z:(YX) is about 0.3, the thermal conductivity and bonding work of the thermal interface material formed after the composition is cured achieve results beyond expectations, with the thermal conductivity increased by 77% and the bonding work increased by 314%.
[0148] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. An organosilicon composition, characterized in that: The composition comprises: a polysiloxane matrix, a thermally conductive inorganic filler, a catalyst and a tackifier; The polysiloxane matrix includes a bisvinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl groups in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol; The mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix is 70% to 110%; The ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the adhesion promoter is 0.1% to 1%; The tackifier includes a hydrogenated silicone resin grafted acrylate tackifier; the content of the vinyl group in the tackifier in the composition is Z mol; Among them, X:Y is 1:(1.5 to 6), and Z:(YX) is (0.01 to 0.6):
1.
2. The composition according to claim 1, characterized in that The tackifier includes A tackifier having a structure as shown in Formula 1 below: Among them, 0 <b≤10,0<c≤10。 3. The composition according to claim 1, characterized in that The Z:(YX) is (0.25 to 0.55): 1; and / or The X:Y is 1:(2.5 to 3.5); and / or The concentration of vinyl groups in the bis-vinyl-terminated polydimethylsiloxane is 0.1wt%-10wt%; and / or The concentration of hydrogen atoms bonded to silicon atoms in the terminal hydrogen-containing polydimethylsiloxane is 0.01 wt % to 2 wt %.
4. The composition according to any one of claims 1 to 3, characterized in that The mass ratio of the thermally conductive inorganic filler to the polysiloxane matrix is 85% to 95%; and / or The thermally conductive inorganic filler is selected from at least one of aluminum powder, aluminum oxide, aluminum nitride powder, boron nitride powder, silicon dioxide powder, zinc oxide, aluminum hydroxide, and magnesium hydroxide; and / or The particle size of the thermally conductive inorganic filler is 0.1 μm to 100 μm.
5. The composition according to any one of claims 1 to 3, characterized in that The ratio of the catalyst to the sum of the mass of the polysiloxane matrix and the adhesion promoter is 0.2% to 0.5%; and / or The catalyst includes a platinum catalyst.
6. A method for preparing an organosilicon composition, characterized in that: The preparation method comprises the following steps: Mixing a thermally conductive inorganic filler with a polysiloxane matrix to obtain a first mixture; adding a tackifier and a catalyst to the first mixture to obtain the organosilicon composition; The polysiloxane matrix comprises a bisvinyl-terminated polydimethylsiloxane and a terminal hydrogen-containing polydimethylsiloxane; the content of vinyl groups in the polysiloxane matrix is X mol; the content of hydrogen atoms bonded to silicon atoms in the polysiloxane matrix is Y mol; the tackifier comprises a hydrogen-containing silicone resin grafted acrylate tackifier; the content of vinyl groups in the tackifier in the composition is Z mol; Among them, X:Y is 1:(1.5 to 6), and Z:(YX) is (0.01 to 0.6):
1.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises: The inorganic filler and the polysiloxane matrix are mixed by first stirring to obtain a first mixture, wherein the rotation speed of the first stirring is 700 r / min to 900 r / min, and the stirring time of the first stirring is 0.5 min to 10 min; and / or The tackifier and the catalyst are added to the first mixture, and the organic silicon composition is obtained by second stirring and third stirring; the second stirring speed is 700 r / min to 900 r / min, and the stirring time of the second stirring is 0.5 min to 10 min; the third stirring speed is 950 r / min to 1100 r / min, and the stirring time of the second stirring is 0.2 min to 1 min; and / or The structure of the tackifier is shown in Formula 1 below: Among them, 0 <b≤10,0<c≤10。 8. A thermal interface material, characterized in that: The thermal interface material is formed by curing the composition according to any one of claims 1 to 5 or the composition obtained by the preparation method according to claim 6 or 7.
9. The thermal interface material according to claim 8, characterized in that: The composition is reacted at a temperature of 80° C. to 200° C. for 1 hour to 24 hours and then cured to form the thermal interface material; and / or The curing process of the composition includes a first curing stage and a second curing stage; the curing temperature of the first curing stage is 80°C to 90°C, and the reaction time of the first curing stage is 1h to 4h; the curing temperature of the second curing stage is 140°C to 160°C, and the reaction time of the second curing stage is 0.5h to 2h.
10. The thermal interface material according to claim 8 or 9, characterized in that: The thermal conductivity of the thermal interface material is 9Wm - 1 K -1 Up to 14Wm -1 K -1 ; and / or The bonding work of the thermal interface material is 650 Jm -2 Up to 2300Jm -2 .
Citation Information
Patent Citations
Thermal interface material as well as preparation method and application thereof
CN118085295A
Cited By
High-thermal-conductivity interface material composition and preparation method thereof
CN120025687A